Chemical Synthesis of a Disaccharide from Vibrio vulnificus Biotype 2 Serovar A O-Antigen Containing a Rare l-GalpNAmA - Zhu, Shengyong; Hu, Jing; You, Qingjun; Tian, Guangzong; Zou, Xiaopeng; Qin, Chunjun; Yin, Jian (Synthesis, 2024)
The bacterium Vibrio vulnificus can cause severe infections internally and externally. The mortality rate of V. vulnificus-associated gangrene and septicemia has increased due to antibiotic resistance and the absence of human vaccine. Bacterial carbohydrates have been widely used in the development of bacterial vaccines. Here, a rare l-GalpNAmA-containing disaccharide that exists in V. vulnificus biotype 2 serovar A O-antigen was synthesized from d-glucose and l-galactose. An investigation on the influence of different linkers on the disaccharide synthetic efficiency indicated that the amine linker has more practicality. Two α-glycosidic linkages were constructed with good stereoselectivity by using nonparticipating C2 azido group and solvent effect. An orthogonal protection strategy allowed introductions of carboxyl and acetamidino (Am) groups at the disaccharide stage. The synthesis of the amine-linked disaccharide will provide a basis for the preparation of the trisaccharide repeating unit and longer fragments of V. vulnificus biotype 2 serovar A O-antigen, as well as other complex glycans.
Keywords: Vibrio vulnificus; O-antigen; oligosaccharide; chemical synthesis; C6 oxidation; acetamidino group